The risk of urban floods caused by precipitation on the example of Bydgoszcz, Poland - Katarzyna Kubiak-Wójcicka; Bogdan Bąk; Mohamed-Sadek Messis (Hungarian Geographical Bulletin)
The article concerns the flood risk assessment in Bydgoszcz in April–October 2010–2022. The distribution of daily precipitation sums for two meteorological stations in Bydgoszcz was analysed. The study confirmed that the risk of extreme precipitation is greatest in the summer months (May–August). It was found that some of the intense rainfall that might cause short-term flooding of urban areas was often local and caused by storm phenomena. Analysis of flood-related interventions by the State Fire Service in Bydgoszcz showed that 2022 had the highest number of incidents (117). The analysis of precipitation and State Fire Service interventions showed a small degree of dependence between the two, both at the city-wide scale and for individual city districts. The spatial distribution of these interventions allowed the Bydgoszcz city districts most exposed to the effects of pluvial flooding to be identified. The work showed the complexity of the issue of urban flood risk, of monitoring such phenomena at the city and district scales, and of countering the effects of such phenomena.